2005
DOI: 10.5688/aj690223
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics and Pharmacogenomics Instruction in Colleges and Schools of Pharmacy in the United States

Abstract: Objectives. To ascertain the extent and depth to which pharmacogenetics/pharmacogenomics is being taught in schools of pharmacy in the United States. To assess perceptions regarding future curricular emphasis dedicated to pharmacogenetics/pharmacogenomics instruction. Methods. A survey was developed based on recommendations provided in a recent report on pharmacogenetics/pharmacogenomics by AACP's Academic Affairs Committee. It was mailed to 85 deans at colleges and schools of pharmacy in the United States. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 4 publications
1
51
0
Order By: Relevance
“…In U.S., seven studies have revealed consistent positive attitudes towards PG among pharmacists; 67% felt that PG should be focal point in patient care, 17 83% of pharmacists believed that genetic can improve patients outcomes, 15 more than half of participants felt that PG can reduce ADRs and has promising benefits to healthcare systems. [16][17][18][19]26 Similar findings were revealed from UK that 80-95% considered PG as beneficial to patients, despite reported gross limited knowledge of PG reflected in only 6% felt well informed about PG; 9 from Malaysia 67% of pharmacists felt that PG is very important in drug safety; 12 these is in agreement with findings from Australia 24 and Nigeria. 20 Recently from Ukraine, 87% of future pharmacists perceived benefits from PG, but only one-third (1/3) of the participants that correctly understood PG and 70% not aware of PG 25 and this is comparable with results from Canada.…”
Section: Attitudes-perceived Benefitssupporting
confidence: 76%
See 2 more Smart Citations
“…In U.S., seven studies have revealed consistent positive attitudes towards PG among pharmacists; 67% felt that PG should be focal point in patient care, 17 83% of pharmacists believed that genetic can improve patients outcomes, 15 more than half of participants felt that PG can reduce ADRs and has promising benefits to healthcare systems. [16][17][18][19]26 Similar findings were revealed from UK that 80-95% considered PG as beneficial to patients, despite reported gross limited knowledge of PG reflected in only 6% felt well informed about PG; 9 from Malaysia 67% of pharmacists felt that PG is very important in drug safety; 12 these is in agreement with findings from Australia 24 and Nigeria. 20 Recently from Ukraine, 87% of future pharmacists perceived benefits from PG, but only one-third (1/3) of the participants that correctly understood PG and 70% not aware of PG 25 and this is comparable with results from Canada.…”
Section: Attitudes-perceived Benefitssupporting
confidence: 76%
“…25 Three surveys were qualitative, that used one or combination of semi structure questionnaire, one-day meeting and case scenarios, 9,22,26 and with regard to design, four research were cohort study, 19,21,24,26 while the rest nine were Crosssectional studies, 9,12,15,16,18,[22][23][24][25] Pharmacogenetics or PG or pharmacogenetic testing and pharmacists or pharmacy students were discussed in all the articles. Table 1 presented the summary of included researches in this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, only 32 out of 41 (78%) pharmacy schools that answered a survey described that they have some components of pharmacogenomics in their curriculum. 27 In 2010, that number grew to 69 out of 75 (92%). 28 However, 40% of these schools offer 10 or fewer didactic hours in pharmacogenomics, 28 and in some situations, pharmacogenomics is offered only as an elective.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacogenomics learning in these SBT courses involves the discussion of particular scenarios, applying and reinforcing the learned concepts as suggested by previous work. 29 Furthermore, this P1 course includes ethical, legal, social and economic implications, as well as metabolomics, epigenetics and bioinformatics, covering some of the suggested additional pharmacist competencies 27,28 that were reported as "deficient" in some schools in the 2010 study. 28 If a patient is an ultra-rapid metabolizer for a specific enzyme, a medication metabolized by that enzyme will _____.…”
Section: Discussionmentioning
confidence: 99%